Keratin 76 is required for tight junction function and maintenance of the skin barrier - DiTommaso, T.; Cottle, D.; Pearson, H.; Schluter, H.; Kaur, Pritinder; Humbert, P.; Smyth, I. (Public Library of Science, 2014)
Keratins are cytoskeletal intermediate filament proteins that are increasingly being recognised for their diverse cellular functions. Here we report the consequences of germ line inactivation of Keratin 76 (Krt76) in mice. Homozygous disruption of this epidermally expressed gene causes neonatal skin flaking, hyperpigmentation, inflammation, impaired wound healing, and death prior to 12 weeks of age. We show that this phenotype is associated with functionally defective tight junctions that are characterised by mislocalization of the integral protein CLDN1. We further demonstrate that KRT76 interacts with CLDN1 and propose that this interaction is necessary to correctly position CLDN1 in tight junctions. The mislocalization of CLDN1 has been associated in various dermopathies, including the inflammatory disease, psoriasis. These observations establish a previously unknown connection between the intermediate filament cytoskeleton network and tight junctions and showcase Krt76 null mice as a possible model to study aberrant tight junction driven skin diseases.